David, Jether, and Child Soldiers - Bosworth, David A. 1972- (2011)
David’s enthusiasm for killing ‘this uncircumcised Philistine’ (1 Sam. 17.26, 36) contrasts with Jether’s refusal to kill Zebah and Zalmunah (Judg. 8.20). David’s victory over Goliath lives in cultural memory as a famous victory of youth over experience and weakness over strength. Jether’s reluctance to kill is almost entirely forgotten. The widespread celebration of the youthful David’s heroics overlooks aspects of the text that characterize David negatively, implicitly denigrates Jether, and tacitly endorses child soldiering. This article contrasts David and Jether and correlates their narratives with information about child soldiers in ancient Israel and the modern world.
Keywords: David -- Israel, König; David und Goliat; Bibel; Kind; Krieg; Killing; Warfare; Child soldiers; Jether; Goliath; David